Better Safe Than Sorry: A Precautionary Toxic Substances Control Act Reform Proposal - Andrew Liebler (Washington University Journal of Law & Policy, 2015)
In 2011, the Natural Resources Defense Council released an issue paper on disease clusters in the United States. The paper documented the phenomenon of unusually large groups of people afflicted with certain diseases in a circumscribed place and time. These heightened incidences of various ailments have been linked to the presence of various toxic chemicals in the environment and consumer products. At the heart of this problem is the failure of America’s primary regulatory safeguard against harmful chemical exposure: the Toxic Substances Control Act (“TSCA”). In response to the TSCA’s shortcomings, this Note argues that the current US chemical regulatory system under the TSCA should be replaced with a regulatory scheme that places the burden on chemical manufacturers to affirmatively prove the safety of their chemicals. While this Note does not purport to specify the exact parameters of a new chemical regulatory system, it does assert a number of important principles that should form the foundation of a new system.
Keywords: Andrew Liebler; Toxic Substances Control Act; TSCA; birth defects; cancer; contamination; strong precautionary principle; Commission Regulation 1907/2006; REACH Regulation